Catalisadores à base de ferro, vanádio e molibdênio suportados em titanatos lamelares e TiO2 comercial na aplicação da reação de NO com NH3 - Grosseli, Guilherme Martins (2011)
The minimization of emissions of nitrogen oxides (NOx) is a subject of great interest because they cause serious environmental problems affecting human health, flora and fauna. To break down the NOx catalytic reduction of these compounds to N2 has acquired great importance and may occur in the absence or presence of a reducing agent. The selective catalytic reduction using ammonia as a reducing agent (NH3-SCR) has been shown to be one of the most attractive, being used worldwide to control NOx emissions by industries due to its high efficiency, selectivity and low cost. To obtain more efficient catalysts for this reaction, several studies have been developed. In this context, the objective of this work is to prepare, to wet impregnation, catalysts based on vanadium, molybdenum and iron supported on commercial TiO2 and lamellar titanates (TL) with high (A-TL) or low-sodium (B-TL), and apply them to the reduction of NO with NH3.It was also studied the effect of calcination temperature in titanates with low sodium content. Results of XRD and adsorption of N2 measurements confirmed the formation of TL mesoporous structure and high specific surface area. After the addition of metal to TiO2 and TL, it was observed a significant decrease in the values of specific surface areas, attributed to the filling of pores by metal oxides. The RTP-H2 showed lower reducibility of metals supported on the lamellar titanates and commercial TiO2 support. The catalysts supported TL with high sodium content showed lower catalytic activity compared to commercial catalysts . However, the catalysts supported on titanates with low sodium content showed promising results in the conversion of NO to N2. The catalysts Fe2O3/TiO2 Fe2O3/B-TL showed loss of activity in the presence of SO2, which partially regenerates in the absence of the compound. In the presence of water, both catalysts showed a decline in the conversion, With the removal of H2O the Fe2O3/TiO2 showed partial regeneration, while the Fe2O3/B-TL suffered irreversible deactivation.